1996
DOI: 10.1097/00004647-199607000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Radiofluorinated L-m-Tyrosines: New In-Vivo Probes for Central Dopamine Biochemistry

Abstract: Summary:In this work, we introduce 6-['sFlfluoro-L-m tyrosine (6-FMT) and compare its in-vivo kinetic and bio chemical behaviors in monkeys and rodents with those of 4-FMT and 6-['sFlfluoro-L-3,4-dihydroxyphenylalanine (DOPA) (FDOPA). These radiofluorinated m-tyrosine presynaptic dopaminergic probes, resistant to peripheral 3-0-methylation, offer a nonpharmacologicai alternative to the use of catechol-O-methyltransferase inhibitors. Like FDOPA, 4-FMT and 6-FMT are analogs that essen tially follow the L-DOPA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…In contrast, although the chemical structure of 11 C-6MemTyr raised the expectation that it is a substrate of peripheral AADC for decarboxylation to facilitate the brain uptake by carbidopa, it was not significantly affected by a clinical bymouth dose of carbidopa. Previous studies using 18 F-FmT demonstrated that the administration of carbidopa increased the level of 18 F-FmT in plasma only by 15% (24) and also that the products of AADC-mediated decarboxylation were detected in plasma even with carbidopa administration (33). To assess the substrate specificity of 11 C-6MemTyr to AADC, carbidopa was intravenously administered to achieve higher plasma concentration than clinical by-mouth administration.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, although the chemical structure of 11 C-6MemTyr raised the expectation that it is a substrate of peripheral AADC for decarboxylation to facilitate the brain uptake by carbidopa, it was not significantly affected by a clinical bymouth dose of carbidopa. Previous studies using 18 F-FmT demonstrated that the administration of carbidopa increased the level of 18 F-FmT in plasma only by 15% (24) and also that the products of AADC-mediated decarboxylation were detected in plasma even with carbidopa administration (33). To assess the substrate specificity of 11 C-6MemTyr to AADC, carbidopa was intravenously administered to achieve higher plasma concentration than clinical by-mouth administration.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of the various enzymes in the metabolic pathway of FMT in the rat are high, e.g., the AAAD activity in rat plasma is 60 pmol/min/ml. Barrio et al showed that even at 5 mg/kg carbidopa there was still peripheral AAAD metabolism [17]. They also showed that the rat striatum contained about half of the 6-[…”
Section: Discussionmentioning
confidence: 99%
“…Both FDOPA and FMT have been used reliably in primates (Bankiewicz et al, 2000; Doudet et al, 1999; Elsinga et al, 2006; Jordan et al, 1997; Yee et al, 2001) as a pre-synaptic marker for the integrity of the nigrostriatal pathway. However, a study in mice found that neither tracer clearly visualized the striatum (Honer et al, 2006), although metabolic studies of FDOPA and FMT unequivocally demonstrate that the label accumulates in dopaminergic structures of the rat brain (Jordan et al, 1997; 1998; Barrio et al, 1996). FMT is not metabolized by catechol-O-methyltransferase, avoiding the need to inhibit that enzyme (Barrio et al, 1996), and one study suggests FMT is superior to FDOPA for visualizing the striatum in monkeys (DeJesus et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in mice found that neither tracer clearly visualized the striatum (Honer et al, 2006), although metabolic studies of FDOPA and FMT unequivocally demonstrate that the label accumulates in dopaminergic structures of the rat brain (Jordan et al, 1997; 1998; Barrio et al, 1996). FMT is not metabolized by catechol-O-methyltransferase, avoiding the need to inhibit that enzyme (Barrio et al, 1996), and one study suggests FMT is superior to FDOPA for visualizing the striatum in monkeys (DeJesus et al, 1997). The FMT serves as a tracer of the aromatic l-amino acid decarboxylase (AADC) enzyme, which traps and accumulates the 18 F metabolites in dopaminergic nerve terminals (Jordan et al, 1997; 1998; Barrio et al, 1996; Bankiewicz et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation